INVESTIGATING MENTAL HEALTH CHALLENGES IN PAKISTANI CHILDREN WITH NEURODEVELOPMENTAL CONDITIONS AT A DEVELOPMENTAL ASSESSMENT SERVICE - Muhammad Muslim Khan; Muhammad Qasim Khan; Amajd Ali Qureshi; Tahir Shahab; Badar Uddin Ujjan; Aurangzeb Kalhoro (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Neurodevelopmental disorders (NDCs) profoundly affect children’s emotional, social, and cognitive development, constituting a substantial proportion of child developmental challenges globally. Objective: The research aimed to investigate past mental health concerns in children with neurodevelopmental conditions attending a developmental assessment service. Methodology: A rigorous mixed-methods strategy is used in this research, which took place at Mardan Medical Complex, Mardan - Pakistan from January to December 2022, to look into mental health issues in 232 children (ages 3 to 12) who have neurodevelopmental abnormalities. Standardized tests, caregiver interviews, and inspections of medical records were all used in the data gathering process. Dissecting correlations between DSM-5 disorders, CBCL profiles, gender, and age is made easier using IBM SPSS statistical analysis tools. Results: A significant gender gap was seen in a group of 232 children (ages 3–12) with 60% neurodevelopmental abnormalities in boys (n=139) and 40% in girls (n=93). ASD (n=63; 27.16%), ADHD (n=53; 22.84%), and Specific Learning Disabilities (n=47; 20.26%) were the most common diagnoses. Analysis showed that there were differences in symptom profiles according to age and gender; with female having greater internalizing scores (25.3) and male having, higher externalizing scores (45.8). The DSM-5 diagnoses and CBCL scores were shown to be significantly correlated, highlighting the intricate relationship between diagnostic and demographic characteristics that shapes the mental health profiles of this vulnerable group. Conclusion: This study highlights the critical need for focused treatments and culturally aware methods to improve the general well-being of children with neurodevelopmental disorders in Pakistan by shedding light on the widespread mental health problems among this population.